ACUTE TOXICITY II: EFFECT OF ORGANOPHOSPHATES AND CARBMATES TO CATLA CATLA FINGERLINGS - Ghazala; S. Mahboob; K. A. Al-Ghanim; S. Sultana; H. F. Alkahem Al- Balawi; T. Sultana; F. Al-Misned; Z. Ahmed (Journal of Animal and Plant Sciences, 2014)
Pesticides are widely used in modern agriculture to aid in the production of high quality food. However, some pesticides have the potential to cause serious health and/or environmental damage. Organophosphates (OCP’S) and carbamates can cause pollution in freshwater ecosystem, as well as having a significant effect on the health of fish. The acute effects of commercial formulation of triazophos, profenofos, carbofuran and carbaryl were determined in one of the indigenous fish species, Catla catla fingerlings. Pesticides were applied to fingerlings that had been grown under optimised standard conditions under a maintained static bioassay system.  Probit analysis was used for the estimation of LC50 values, which were ascertained as 4.84, 0.19, 0.99 and 7.89 mg/L for triazophos, profenofos, carbofuran and carbaryl, respectively. 100% mortality of Catla catla was observed with a 2.8 mg/L dose of carbofuran at 96 hours with a significant difference.  Acute toxic stress was noticed with subjects exhibiting behavioral intoxication, including suffocation, lying on the bottom, erratic swimming, lethargy and downward movements and gulping prior to mortality.
Keywords: Catla catla; Acute toxicity; Profenofos; Triazophos; Carbofuran; Carbaryl